Teacher-Traineesâ Perceptions of ICT (Information Communication Technology) Integration in Nigerian Teacher Education Programme - Thomas, Olusola Angelina; Oladejo, Maruff Akinwale (EDUCARE, 2017)
ABSTRACT: Teaching nowadays is fast expanding rapidly and it requires modern technologies to provide more flexible and effective ways of improving teacher education, and connecting teachers to the global community. ICT (Information and Communication Technology) integration into teacher education, therefore, is the key to equipping and producing professional teachers as well as improved pedagogy. However, there is the need to consider the type and nature of teacher trainees before integrating ICT in teacher education programmes, because their perceptions are likely to differ. This study, therefore, focuses on the perceptions of teacher trainees (regular and sandwich students) regarding the integration of ICT in teacher education programme at the UNILAG (University of Lagos) in Akoka, Nigeria. It adopted the descriptive research design. Two hundred and fifty participants were involved. One research question and two hypotheses, based on the specific purposes, were raised and answered in the study. A self-constructed validated and reliable instrument was used to collect data. Results revealed that teacher trainees are favourably disposed to the integration of ICT into teacher education as indicated by the grand mean and standard deviation (M = 3.22; SD = 12.22). Significant differences in the perceptions of teacher-trainees regarding the integration of ICT in teacher education programme based on type of the programme was also discovered (t-cal = -2.315; df = 98; P < .05). Teacher-trainees have to realise that ICT has come to stay in their programme. They need to develop more confidence in their individual ability at becoming computer literate teachers in order to remain relevant in the modern day information age. KEY WORDS: Teacher Education; Information and Communication Technology; Teacher-Trainees; Perceptions; Computer Literate Teachers.Â Â About the Authors: Dr. Olusola Angelina Thomas is an Academic Staff at the Department of Educational Administration UNILAG (University of Lagos) in Akoka, Nigeria; and Dr. Maruff Akinwale Oladejo is currently a Lecturer at the Department of Educational Administration UNILAG in Akoka, Nigeria. For academic interests, the authors can be contacted via their e-mails at: soowler@yahoo.com and maoladejo@unilag.edu.ngSuggested Citation: Thomas, Olusola Angelina & Maruff Akinwale Oladejo. (2017). âTeacher-Traineesâ Perceptions of ICT (Information Communication Technology) Integration in Nigerian Teacher Education Programmeâ in EDUCARE: International Journal for Educational Studies, Volume 10(1), August, pp.1-10. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-7877. Article Timeline: Accepted (February 22, 2017); Revised (May 20, 2017); and Published (August 30, 2017).